Da una generazione all'altra: Le riviste di Pagliarani (TEST Ticontre. Theory Text Translation, 2020)
The essay reconstructs the history of Elio Pagliarani's twp journals, «Periodo ipotetico» and`«Ritmica», outlining the political-cultural scenario within which they were active. In particular, is highlighted the work done by Pagliarani himself, who accompanied and encouraged the transition from the neo-avant-garde generation to that of Gruppo 93.
Keywords: Riviste di poesia; Periodo ipotetico; Ritmica; Poesia contemporanea; Elio Pagliarani